CC3 & CC5 demarcation layout of B1-12F (RFA-516_Rev.D) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF version of drawings.